2021
DOI: 10.5539/elt.v14n6p96
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse and Counterargument Integration in Student Argumentative Papers

Abstract: Incorporating counterarguments can be challenging for many student-writers, including those for whom English is a second or other language. In this study, we present findings that may lead to improvements in students’ understanding of the benefits of integrating counterarguments. In our study, expert readers were presented with excerpts of student academic writing in order to assess the degree to which counterarguments could be identified through student deployment of metadiscoursal features. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…The recent results, as presented in Figures 8 and 9, focusing on the firstlowest and second-lowest scoring students, highlight the importance of effective refutation in addressing the misuse of AI. This aligns with the emphasis from the previous study, which stated that while articulating a robust thesis and providing supporting evidence is crucial, acknowledging opposing viewpoints enhances the depth and credibility of the overall argument (McCarthy et al, 2021). Specifically, Figures 8 and 9 in the present study recommend that both low-scoring students incorporate more detailed examples and furnish more substantial evidence to strengthen their arguments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The recent results, as presented in Figures 8 and 9, focusing on the firstlowest and second-lowest scoring students, highlight the importance of effective refutation in addressing the misuse of AI. This aligns with the emphasis from the previous study, which stated that while articulating a robust thesis and providing supporting evidence is crucial, acknowledging opposing viewpoints enhances the depth and credibility of the overall argument (McCarthy et al, 2021). Specifically, Figures 8 and 9 in the present study recommend that both low-scoring students incorporate more detailed examples and furnish more substantial evidence to strengthen their arguments.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, including counterarguments is imperative for cultivating a nuanced and compelling discourse. While articulating a robust thesis and providing supporting evidence is essential, acknowledging opposing viewpoints enhances the depth and credibility of the overall argument (McCarthy et al, 2021). Previous research has indicated that an excellent essay articulates a distinct perspective supported by logical arguments and addresses opposing viewpoints with evidence, highlighting the importance of critical thinking (Noroozi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%